PSR J1141-6545: A powerful laboratory of GR and tensor-scalar theories of gravity - Verbiest, J.; Bhat, Ramesh; Bailes, M. (2012)
Pulsars in close binary systems have provided some of the most stringent tests of strong- field gravity to date. The pulsar{white-dwarf binary system J11416545 is specifically interesting due to its gravitational asymmetry, which makes it one of the most powerful probes of tensor-scalar theories of gravity. We give an overview of current gravitational tests provided by the J11416545 binary system and comment on how anomalous accelerations, geodetic precession and timing instabilities may be prevented from limiting future tests of gravity to come from this system. Keywords: Pulsars; tensor-scalar theories. Copyright © 2012 by World Scientific Publishing Co. Pte. Ltd.